Chronology of Malaysia halal industry development - Zakaria, Muhammad Hafeez; Abdul Kadir, Mohammad Nidzam; Ab. Razak, Ratna Roshida; Awang, Mohd. Daud; Mohammad Yusoff, Mohd Haniff (Human Resource Management Academic Research Society, 2024)
The high demand for products with halal certification by Muslim consumers helps them to make wise decisions about the products that they should purchase and cast away their feelings of uncertainty. To meet the needs of consumers for halal products, the process of halal industry development in Malaysia started 60 years ago with strategies and planning. This timeline covers developments and historical occurrences that have relevance to Malaysia's halal sector development from 1957 to 2020. The halal business continued to grow and prosper annually. The Malaysian government and businesspeople worked very hard in the halal sector. The Second Industry Master Plan (1996-2005), the Third Industrial Master Plan (2006-2020), the Ninth Malaysia Plan (1998-2010), and the National Agriculture Policy (1998- 2010) all mention the halal industry. It has given Malaysia numerous benefits today, helping the country become a leader in this field. In addition to satisfying Muslim consumers' needs, this sector is crucial for raising governmental revenue